2015
DOI: 10.1371/journal.pone.0116110
|View full text |Cite
|
Sign up to set email alerts
|

Association between Lipid Ratios and Insulin Resistance in a Chinese Population

Abstract: AimTo explore the association of lipid ratios and triglyceride (TG) with insulin resistance (IR) in a Chinese population. We also provide the clinical utility of lipid ratios to identify men and women with IR.MethodsThis cross-sectional study included 614 men and 1055 women without diabetes. Insulin resistance was defined by homeostatic model assessment of IR > 2.69. Lipid ratios included the TG/ high density lipoprotein cholesterol (HDL-C), the total cholesterol (TC)/HDL-C and the low density lipoprotein chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 33 publications
(72 reference statements)
3
27
1
5
Order By: Relevance
“…Furthermore, insulin resistance induces disturbances in muscle fatty acid handling, and this underlies the associated increase in serum triglycerides and decrease in HDL . Conversely, LDL levels appear to be mainly determined by genetics, with insulin resistance having less influence …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, insulin resistance induces disturbances in muscle fatty acid handling, and this underlies the associated increase in serum triglycerides and decrease in HDL . Conversely, LDL levels appear to be mainly determined by genetics, with insulin resistance having less influence …”
Section: Discussionmentioning
confidence: 99%
“…According to the ATPIII and JIS criteria, the optimal cutoff for TG/HDL-C was 1.6 and 1.2 in men and 1.1 and 1.1 in women, respectively. The cutoff values of the markers to detect the MetS in Guangdong women is 0.88 [ 30 ] and 0.84 in Zhuhai women [ 31 ]; the cutoff value in Ghanaian women is 0.61 [ 32 ]. In Canada, men and women is 1.62 and 1.18, respectively [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation of TG/HDL-C, TC/HDL-C with HOMA-IR has been demonstrated among PCOS women in China [24] and T2DM in Thailand [26]. Results of some studies also supported that TG/HDL-C ratio could be used as an indicator of IR among some population including the middle-aged and elderly population in Taiwan [16], euthyroid normal-weight healthy adults in Peru [27], PCOS patients in India [28] and in Chinese population without diabetes [29]. A large scale cross-sectional analysis among Chinese adults also indicated that TG/HDL-C ratio and TyG index are useful markers in estimating IR and TyG index is the best indicator for assessing the risk of IR [30].…”
Section: Discussionmentioning
confidence: 89%